Redox-Modulatory and MET-Inhibitory Triad: Synergistic Cytotoxicity of L-cysteine, NAC, and MET Inhibition in Cervical Cancer Cells - Tassanbiyeva , Aigerim; Onggarbek , Aruzhan; Xie , Yingqiu (Eurasian Journal of Applied Biotechnology, 2025)
Background: The MET signaling pathway is a central regulator of tumor growth, epithelial-to- mesenchymal transition (EMT), and therapy resistance. However, MET inhibition alone may be insufficient due to compensatory signaling and intrinsic redox buffering. N-acetylcysteine (NAC) and L-cysteine, as thiol-based antioxidants, regulate intracellular glutathione pools and redox- sensitive signaling cascades. We investigated whether combining NAC and L-cysteine with MET inhibition could enhance anticancer efficacy without exogenous oxidative stress or chemotherapy. Materials and methods: Human (HeLa, K562) and murine (B16, Myc-CaP) cancer cell lines were treated with L-cysteine, NAC, crizotinib (a clinically relevant MET inhibitor), or their combinations. Phospho-MET (pMET) expression was analyzed by confocal immunofluorescence microscopy with DAPI counterstaining. Cell death was quantified by flow cytometry using Hoechst and PI staining. Results: L-cysteine/NAC alone did not reduce cell death, but in combination increased cytotoxicity across tested cell lines. The triple treatment (L-cysteine, NAC, crizotinib) significantly suppressed pMET activation, showing reduced fluorescence intensity and perinuclear redistribution. Flow cytometry demonstrated a robust increase in late apoptosis in the triple combination group compared with monotherapies or dual treatments (p < 0.0001). Mechanistically, redox stabilization appeared to sensitize cells to MET inhibition by limiting compensatory pro-survival pathways. Inhibitor screening suggested the involvement of AKT and p38 signaling in the NAC/L-cysteine–mediated ROS-independent mechanism. Conclusion: The tri-modal strategy combining L-cysteine, NAC, and MET inhibition demonstrates robust and synergistic cytotoxicity in cancer cells, independent of exogenous oxidative or chemotherapeutic stress. These findings implicate a novel therapeutic paradigm in which redox modulation enhances oncogene-targeted interventions. This combinatorial framework holds promise not only for augmenting MET-targeted therapies but also for mitigating adverse effects such as chemotherapy-induced alopecia, given the known protective roles of NAC and METi in hair follicle stem cell maintenance. Acknowledgement: The study was supported by Nazarbayev University and the L. N. Gumilyov Eurasian National University. Key words: MET kinase, Redox regulation, Cysteine metabolism References: Smith, J.A., Nguyen, T.T., Patel, R. et al. Role of hydroxyapatite coatings in enhancing osteoblast adhesion and proliferation. Biomaterials 274, 120857 (2021). Twardowski, P., Smith, D.C., Ball, E.D. et al. Crizotinib in MET-amplified advanced solid tumors: results of a phase I trial. J. Clin. Oncol. 34, 3293–3299 (2016). Manna, S.K., Zhang, H.J., Yan, T. et al. Overexpression of redox regulatory protein thioredoxin activates NF-κB and AP-1 transcription factors. Cancer Res. 60, 4321–4327 (2000). Lu, S.C. Regulation of glutathione synthesis. Mol. Aspects Med. 30, 42–59 (2009). Engelman, J.A., Zejnullahu, K., Mitsudomi, T. et al. MET amplification leads to gefitinib resistance in lung cancer by activating ERBB3 signaling. Science 316, 1039–1043 (2007).